A simple wet grinding preparation method and application of high entropy oxide negative electrode materials for lithium ion batteries
Synthesizing high-entropy oxide materials through wet grinding method solves the volume expansion problem of lithium-ion battery negative electrode materials, achieves high capacity, excellent rate performance and long cycle stability, and is suitable for large-scale production.
Patent Information
- Application Number
- CN202310231419.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-07
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2043-03-07
AI Technical Summary
The volume expansion of the negative electrode material of traditional lithium-ion batteries seriously affects its long cycle stability, and the existing improvement measures are complex and are not suitable for large-scale synthesis.
A high entropy oxide material (Mn0.2Fe0.2Co0.2Cr0.1Zn0.2)3O4 was synthesized by a simple wet grinding method, and a material with uniform particle size and fine particle size was obtained by high temperature calcination.
It achieves high specific capacity, excellent rate performance and long cycle stability, and is simple in preparation and can be mass-produced.
Smart Images

Figure CN116216787B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a negative electrode material of a lithium ion battery made of a high entropy oxide material, and belongs to the field of energy storage. Background Art
[0002] Lithium-ion batteries have attracted extensive research due to their high energy density and have now been commercialized on a large scale. The negative electrode is an important component of lithium-ion batteries. According to the type of redox reaction, it can be divided into intercalation materials, conversion materials and alloy materials. Conversion materials have attracted widespread attention due to their higher capacity than intercalation materials and smaller volume expansion than alloy materials. However, their volume expansion still seriously affects their long-cycle stability. Traditional improvement measures generally involve structural modifications to improve their cycle stability, but such methods are not suitable for large-scale synthesis due to the complex synthesis method. To this end, we designed a simple wet grinding method for synthesizing high-entropy oxide materials with excellent cycle stability. Summary of the invention
[0003] Purpose of the invention: In view of the technical problems existing in the above-mentioned prior art, the present invention provides a preparation method and application of a high entropy oxide negative electrode material for lithium-ion batteries with high specific capacity, excellent rate performance and long cycle stability. We obtain a high entropy oxide material (Mn) by a simple wet grinding and high temperature calcination method. 0.2 Fe 0.2 Co 0.2 Cr 0.1 Zn 0.2 )3O4, the high entropy oxide material prepared by this method has uniform and small particle size, and the size is about 100-200nm, which can effectively accelerate the transmission of ions and electrons, so that the material we synthesized has better capacity and rate performance for lithium-ion battery negative electrode. In addition, the preparation method is simple, can be scaled up for production, and the operation steps are highly controllable.
[0004] In order to solve the technical problem of the present invention, the technical scheme proposed is: a simple wet grinding preparation method for high entropy oxide negative electrode materials for lithium ion batteries, wherein 6 mM of manganese nitrate, iron nitrate, cobalt nitrate, chromium nitrate and zinc acetate are placed in a 100 ml flask according to a molar ratio of 2:2:2:1:2, 30 ml of water is added, the beaker is transferred to a stirring table, and stirred continuously at room temperature. During the stirring process, an appropriate amount of ammonia water is added, the pH of the solution is adjusted to 8, and the stirring is carried out for 10 min to 30 min at a stirring speed of 300 to 800 r / min. The precursor solution was transferred to a ball mill for ball milling at a speed of 400 r / min for 4 h. The brown solution obtained after ball milling was centrifuged twice with water and then once with ethanol. The brown block solid was dried in an ordinary oven at 50-80°C for 12 h to obtain a brown powder. Subsequently, the brown powder was transferred to a muffle furnace and heated to 900°C in air for calcination at a heating rate of 5°C / min for 3 h. After the calcination, the brown powder was immediately transferred to air for air cooling to obtain a black solid powder -(Mn 0.2 Fe 0.2 Co 0.2 Cr 0.1 Zn 0.2 )3O4.
[0005] Preferably, a simple process flow of wet ball milling and high-temperature sintering is used to form a high-entropy oxide material precursor for the negative electrode of a lithium-ion battery by simple ball milling, and then the desired high-entropy oxide material is obtained by sintering.
[0006] Preferably, the specific steps are as follows: add the required metal salt material into a beaker, add a certain amount of deionized water, stir evenly at room temperature, then add a certain amount of ammonia water, put the resulting precipitate into a ball mill for ball milling, and then centrifuge and dry the ball-milled precursor material to obtain a precursor for preparing a high entropy oxide material.
[0007] Preferably, the sample centrifugally dried after ball milling is simply ground and then sintered at high temperature in air in a muffle furnace to obtain the desired high entropy oxide material.
[0008] Preferably, during the stirring at room temperature, the stirring speed is 500 r / min and the stirring time is 10 min.
[0009] Preferably, during centrifugal drying, the washing solution is ethanol or an aqueous solution, and the drying temperature is 60°C.
[0010] In order to solve the technical problem of the present invention, another technical solution is proposed: a high entropy oxide negative electrode material (Mn 0.2 Fe0.2 Co 0.2 Cr 0.1 Zn 0.2 )3O4.
[0011] In order to solve the technical problem of the present invention, another technical solution is proposed: the application of the high entropy oxide negative electrode material for lithium ion batteries is to synthesize the high entropy oxide material (Mn 0.2 Fe 0.2 Co 0.2 Cr 0.1 Zn 0.2 )3O4 is used to prepare the negative electrode of lithium-ion batteries.
[0012] Preferably, the synthesized high entropy oxide material (Mn 0.2 Fe 0.2 Co 0.2 Cr 0.1 Zn 0.2 )3O4, Super P and CMC were mixed in a mass ratio of 7:2:1 with a total mass of 200 mg. 600 ul of water was added and the mixture was placed on a stirring table and stirred at room temperature for 12 h. The mixed material was then coated on a copper foil and dried in a vacuum oven at 60°C for 6 h. The electrode sheets were cut into 14 mm in diameter using a cutting machine. Finally, a button cell was assembled using a lithium sheet as the counter electrode, polypropylene (PP) as the diaphragm, and 1 M LiPF6 dissolved in equimolar ratios of EC and DEC as the electrolyte.
[0013] The present invention discloses a method for preparing a high entropy oxide negative electrode material, wherein high entropy refers to a combination of five or more elements in nearly equal atomic ratios, and the high entropy oxide negative electrode material is obtained by simple wet grinding and sintering. The preparation method comprises the following steps:
[0014] Step (a): preparing a high entropy oxide precursor: adding the required metal salt to a beaker containing an aqueous solution, adding a certain amount of ammonia water to adjust the pH value of the solution while stirring at room temperature, and then transferring the precursor solution to a ball mill for ball milling. After the ball milling, centrifugal washing and drying are performed to obtain a brown block solid. The brown block solid is simply ground to obtain a high entropy oxide precursor powder.
[0015] Step (ii): Preparation of high entropy oxide material: The brown high entropy oxide precursor powder is transferred to a muffle furnace and calcined at high temperature in air. After calcination, it is quickly transferred outside the furnace for air cooling to finally obtain the desired high entropy oxide material.
[0016] Beneficial effects:
[0017] From the perspective of the method, the conventional dry grinding method takes a long time to prepare, usually requiring ball milling for more than 12 hours, and some even require 36 hours. In addition, the materials prepared by the dry grinding method generally have a relatively coarse particle size, usually irregular particles in the micron level. We obtain high-entropy oxide materials through simple wet grinding and high-temperature calcination methods. The high-entropy oxide materials prepared by this method have uniform and small particle sizes, all around 100 to 200 nm, which can effectively accelerate the transmission of ions and electrons, making the materials we synthesized have more excellent capacity and rate performance. In addition, the preparation method is simple, can be scaled up for production, and the operation steps are highly controllable.
[0018] From the perspective of materials, the material is composed of five or more metal elements. The inventors have screened the appropriate element selection and combination through a large number of experiments to effectively adjust the electrochemical properties of the synthesized high-entropy oxide negative electrode material, selectively optimize it according to the desired effect, and combine the advantages of the high-entropy material itself to obtain a lithium-ion battery negative electrode material with high capacity, excellent rate performance and long cycle stability.
[0019] In Comparative Example 1, Mg was used instead of Zn to synthesize another high entropy oxide material. Its specific capacity was significantly reduced compared with the high entropy oxide material in Example 3. This is because the inactive element Mg does not provide additional capacity to the material, thereby reducing the rate performance of the material. Therefore, the appropriate element selection is very important for improving the electrochemical performance of the material.
[0020] In combination with Examples 1-3, a single-phase spinel structured high-entropy oxide material was successfully synthesized by a simple wet grinding process. The particle size was small and uniform, the element distribution was very uniform, and there was no element segregation, which was consistent with the XRD results. Among the three high-entropy oxide materials synthesized with different proportions, they all had very excellent rate performance. By further screening the element content, it was found that (Mn 0.2 Fe 0.2 Co 0.2 Cr 0.1 Zn 0.2 )3O4 has the best rate performance, which is due to the reduction of the content of Cr, which provides less capacity during the electrochemical reaction, while retaining the content of Fe, which has high conductivity and higher capacity, so that its rate performance is further optimized. Its capacity is 907mAh g at a current density of 0.1A g-1. -1 , at 5Ag -1 At high rate, the capacity is still 515.3 mAh g -1 , which is in 2Ag -1 After 100 cycles at a current density of 1.34 mAh g -1The specific capacity of the battery is about 98%. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] The present invention will be further described below in conjunction with the accompanying drawings.
[0022] Figure 1 This is the XRD image of the nano-sized high entropy oxide material obtained in Example 1.
[0023] Figure 2 This is a SEM image of the nano-sized high entropy oxide obtained in Example 1.
[0024] Figure 3 This is an EDS image of the nano-sized high entropy oxide obtained in Example 1.
[0025] Figure 4 The rate performance comparison of high entropy oxides with different proportions obtained in Examples 1-3 and (Mn 0.2 Fe 0.2 Co 0.2 Cr 0.1 Zn 0.2 )Image of the long-cycle performance of 3O4.
[0026] Figure 5 This is the rate performance image of the nano-sized high entropy oxide obtained in Comparative Example 1. DETAILED DESCRIPTION
[0027] Example 1
[0028] Manganese nitrate, iron nitrate, cobalt nitrate, chromium nitrate and zinc acetate were placed in a 100 ml flask at a molar ratio of 2:2:2:1:2, and 6 mM of each was added. 30 ml of water was added, and the beaker was transferred to a stirring table. The mixture was stirred continuously at room temperature. During the stirring process, an appropriate amount of ammonia water was added to adjust the pH of the solution to 8. The mixture was stirred for 10 min at a stirring speed of 500 r / min. The precursor solution was transferred to a ball mill for ball milling at a speed of 400 r / min for 4 h. The brown solution obtained after ball milling was centrifuged twice with water and once with ethanol. The mixture was dried in an ordinary oven at 60°C for 12 h to obtain a brown block solid. The solid was ground to obtain a brown powder. Subsequently, the brown powder was transferred to a muffle furnace and heated to 900°C in air for calcination at a heating rate of 5°C / min for 3 h. After the calcination, the mixture was immediately transferred to air for air cooling to obtain a black solid powder -(Mn 0.2 Fe 0.2 Co 0.2 Cr 0.1 Zn 0.2 )3O4. Figure 1XRD characterization shows that the material we synthesized has a typical spinel structure. Figure 2 The high- and low-magnification SEM images show that the particle size is uniform, about 100 to 200 nm. Figure 3 The EDS element distribution diagram shows that the various elements are distributed very evenly, without obvious element segregation.
[0029] During the battery manufacturing process, we mixed the synthesized high-entropy oxide material, Super P and CMC in a mass ratio of 7:2:1, with a total mass of 200 mg, added 600 ul of water, placed it on a stirring table and stirred at room temperature for 12 hours, then coated the stirred material on a copper foil, dried it in a vacuum oven at 60°C for 6 hours, and cut it into electrode sheets with a diameter of 14 mm using a cutting machine. Finally, we used lithium sheets as counter electrodes, polypropylene (PP) as separators, and 1M LiPF6 dissolved in equimolar ratios of EC and DEC as electrolytes to assemble button batteries.
[0030] Finally, we tested the rate performance and long cycle stability of the assembled battery. The results are as follows: Figure 4 As shown, the test voltage is 0.1~3V, and the test equipment is the Xinwei battery test system, which is at 0.1A g -1 The capacity is 907 mAh g -1 , at 5A g -1 At high rate, the capacity is still 515.3 mAh g -1 , which is at 2A g -1 After 100 cycles at a current density of 1.34 mAh g -1 The specific capacity of the battery is about 98%.
[0031] Example 2
[0032] Manganese nitrate, iron nitrate, cobalt nitrate, chromium nitrate and zinc acetate were placed in a 100 ml flask at a molar ratio of 2:2:2:2:2, 6 mM each, 30 ml of water was added, the beaker was transferred to a stirring table, and the mixture was stirred continuously at room temperature. During the stirring process, an appropriate amount of ammonia water was added to adjust the pH of the solution to 8, and the mixture was stirred for 10 min at a stirring speed of 500 r / min. The precursor solution was transferred to a ball mill for ball milling at a speed of 400 r / min for 4 h. The brown solution obtained after ball milling was centrifuged twice with water, and then once with ethanol, and dried in an ordinary oven at 60°C for 12 h to obtain a brown block solid. The solid was ground to obtain a brown powder. Subsequently, the brown powder was transferred to a muffle furnace, heated to 900°C in air for calcination at a heating rate of 5°C / min and a holding time of 3 h. After the calcination, the mixture was immediately transferred to air for air cooling to obtain a black solid powder -(Mn0.2 Fe 0.2 Co 0.2 Cr 0.2 Zn 0.2 )3O4. Because the method used is the same as that in Example 1, only the ratio of metal elements is modified. Therefore, the synthesized material is a typical spinel structure, and its particle size is also 100-200nm. Its various elements are distributed very evenly without obvious element segregation.
[0033] During the battery manufacturing process, we mixed the synthesized high-entropy oxide material, Super P and CMC in a mass ratio of 7:2:1, with a total mass of 200 mg, added 600 ul of water, placed it on a stirring table and stirred at room temperature for 12 hours, then coated the stirred material on a copper foil, dried it in a vacuum oven at 60°C for 6 hours, and cut it into electrode sheets with a diameter of 14 mm using a cutting machine. Finally, we used lithium sheets as counter electrodes, polypropylene (PP) as separators, and 1M LiPF6 dissolved in equimolar ratios of EC and DEC as electrolytes to assemble button batteries.
[0034] Finally, we tested the rate performance and long cycle stability of the assembled battery. The results are as follows: Figure 4 As shown, the test voltage is 0.1~3V, and the test equipment is the Xinwei battery test system, which is at 0.1A g -1 The capacity is 878.9 mAh g -1 , at 5A g -1 At high rate, the capacity is still 405.6 mAh g -1 , its rate performance is lower than that of Example 1.
[0035] Example 3
[0036] Manganese nitrate, iron nitrate, cobalt nitrate, chromium nitrate and zinc acetate were placed in a 100 ml flask at a molar ratio of 2:1:2:1:2, 6 mM each, and 30 ml of water was added. The beaker was transferred to a stirring table and stirred continuously at room temperature. During the stirring process, an appropriate amount of ammonia water was added to adjust the pH of the solution to 8, and the mixture was stirred for 10 min at a stirring speed of 500 r / min. The precursor solution was transferred to a ball mill for ball milling at a speed of 400 r / min for 4 h. The brown solution obtained after ball milling was centrifuged twice with water, and then once with ethanol, and dried in an ordinary oven at 60°C for 12 h to obtain a brown block solid. The solid was ground to obtain a brown powder. Subsequently, the brown powder was transferred to a muffle furnace and heated to 900°C in air for calcination at a heating rate of 5°C / min for 3 h. After the calcination, the mixture was immediately transferred to air for air cooling to obtain a black solid powder -(Mn0.2 Fe 0.1 Co 0.2 Cr 0.1 Zn 0.2 )3O4. Because the method used is the same as that in Example 1, only the ratio of metal elements is modified. Therefore, the synthesized material is a typical spinel structure, and its particle size is also 100-200nm. Its various elements are distributed very evenly without obvious element segregation.
[0037] During the battery manufacturing process, we mixed the synthesized high-entropy oxide material, Super P and CMC in a mass ratio of 7:2:1, with a total mass of 200 mg, added 600 ul of water, placed it on a stirring table and stirred at room temperature for 12 hours, then coated the stirred material on a copper foil, dried it in a vacuum oven at 60°C for 6 hours, and cut it into electrode sheets with a diameter of 14 mm using a cutting machine. Finally, we used lithium sheets as counter electrodes, polypropylene (PP) as separators, and 1M LiPF6 dissolved in equimolar ratios of EC and DEC as electrolytes to assemble button batteries.
[0038] Finally, we tested the rate performance and long cycle stability of the assembled battery. The results are as follows: Figure 4 As shown, the test voltage is 0.1~3V, and the test equipment is the Xinwei battery test system, which is at 0.1A g -1 The capacity is 870.2 mAh g -1 , at 5A g -1 At high rate, the capacity is still 405.6 mAh g -1 , its rate performance is lower than that of Examples 1 and 2.
[0039] In summary, we have successfully synthesized a single-phase spinel high-entropy oxide material through a simple wet grinding process. The particle size is small and uniform, the element distribution is very uniform, and there is no element segregation, which is consistent with the XRD results. Among the three high-entropy oxide materials synthesized by us with different proportions, they all have very excellent rate performance. By further screening the element content, it is found that as shown in Example 1 (Mn 0.2 Fe 0.2 Co 0.2 Cr 0.1 Zn 0.2 )3O4 has the best rate performance, which is due to the fact that we reduced the content of Cr, which provides less capacity during the electrochemical reaction, while retaining the content of Fe, which has high conductivity and higher capacity, so that its rate performance has been further optimized.
[0040] Comparative Example 1
[0041] Manganese nitrate, iron nitrate, cobalt nitrate, chromium nitrate and magnesium nitrate were placed in a 100 ml flask at a molar ratio of 2:2:2:2:2, 6 mM each, 30 ml of water was added, the beaker was transferred to a stirring table, and the mixture was stirred continuously at room temperature. During the stirring process, an appropriate amount of ammonia water was added to adjust the pH of the solution to 8, and the mixture was stirred for 10 min at a stirring speed of 500 r / min. The precursor solution was transferred to a ball mill for ball milling at a speed of 400 r / min for 4 h. The brown solution obtained after ball milling was centrifuged twice with water, and then once with ethanol, and dried in an ordinary oven at 60°C for 12 h to obtain a brown block solid. The solid was ground to obtain a brown powder. Subsequently, the brown powder was transferred to a muffle furnace, heated to 900°C in air for calcination at a heating rate of 5°C / min and a holding time of 3 h. After the calcination, the mixture was immediately transferred to air for air cooling to obtain a black solid powder -(Mn 0.2 Fe 0.2 Co 0.2 Cr 0.2 Mg 0.2 )3O4. Because the method used is the same as that in Example 2, only the type of metal element is modified, and the Zn element is replaced by the Mg element. Therefore, the synthesized material is a typical spinel structure, and its particle size is also 100-200nm. The distribution of various elements is very uniform, and there is no obvious element segregation.
[0042] During the battery manufacturing process, we mixed the synthesized high-entropy oxide material, Super P and CMC in a mass ratio of 7:2:1, with a total mass of 200 mg, added 600 ul of water, placed it on a stirring table and stirred at room temperature for 12 hours, then coated the stirred material on a copper foil, dried it in a vacuum oven at 60°C for 6 hours, and cut it into electrode sheets with a diameter of 14 mm using a cutting machine. Finally, we used lithium sheets as counter electrodes, polypropylene (PP) as separators, and 1M LiPF6 dissolved in equimolar ratios of EC and DEC as electrolytes to assemble button batteries.
[0043] Finally, we tested the rate performance and long cycle stability of the assembled battery. The results are as follows: Figure 5 As shown, the test voltage is 0.1~3V, and the test equipment is the Xinwei battery test system, which is at 0.1A g -1 The capacity is 715.9 mAh g -1 , at 5A g -1 At high rate, the capacity is 254.2 mAh g -1 .
[0044] We used Mg instead of Zn to synthesize another high entropy oxide material, and its specific capacity was significantly reduced compared with the high entropy oxide material in Example 3. This is because the inactive element Mg does not provide additional capacity to the material, thereby reducing the rate performance of the material. Therefore, the appropriate element selection is very important for improving the electrochemical performance of the material.
[0045] The present invention is not limited to the specific technical solutions described in the above embodiments, and all technical solutions formed by equivalent replacement are within the protection scope required by the present invention.
Claims
1. An application of a high entropy oxide negative electrode material for lithium-ion batteries, characterized in that: The synthesized high entropy oxide anode material (Mn 0.2 Fe 0.2 Co 0.2 Cr 0.1 Zn 0.2 )3O4 is used to prepare negative electrodes for lithium-ion batteries; (Mn 0.2 Fe 0.2 Co 0.2 Cr 0.1 Zn 0.2 The simple wet grinding preparation method of )3O4 is as follows: put 6 mM of manganese nitrate, iron nitrate, cobalt nitrate, chromium nitrate and zinc acetate in a molar ratio of 2:2:2:1:2 in a 100 ml flask, add 30 ml of water, transfer the beaker to a stirring table, stir continuously at room temperature, add an appropriate amount of ammonia water during stirring, adjust the pH of the solution to 8, stir for 10 min, and stir at a speed of 500 r / min. Transfer the precursor solution to a ball mill for ball milling at a speed of 400 r / min for 4 h. Centrifuge the brown solution obtained after ball milling twice with water, then centrifuge it once with ethanol, and dry it in an ordinary oven at 60°C for 12 h to obtain a brown block solid. Grind the solid to obtain a brown powder. Subsequently, transfer the brown powder to a muffle furnace, heat it to 900°C in air for calcination at a heating rate of 5°C / min and a holding time of 3 h. After calcination, immediately transfer it to air for air cooling to obtain a black solid powder -(Mn 0.2 Fe 0.2 Co 0.2 Cr 0.1 Zn 0.2 )3O4; The synthesized high entropy oxide material (Mn 0.2 Fe 0.2 Co 0.2 Cr 0.1 Zn 0.2 )3O4, Super P and CMC were mixed in a mass ratio of 7:2:1 with a total mass of 200 mg. 600 μL of water was added and the mixture was placed on a stirring table and stirred at room temperature for 12 h. The mixed materials were then coated on a copper foil and dried in a vacuum oven at 60 °C for 6 h. The electrodes were cut into 14 mm diameter sheets with a sheet cutter. Finally, a button cell was assembled using a lithium sheet as the counter electrode, polypropylene as the separator, and 1 M LiPF6 dissolved in equimolar ratios of EC and DEC as the electrolyte.
2. The use of high entropy oxide negative electrode material for lithium ion batteries according to claim 1, characterized in that: The button battery was tested for rate performance and long cycle stability at a test voltage of 0.1-3 V using a Xinwei battery test system at 0.1 A g -1 The capacity is 907 mAh g -1 , at 5 A g -1 At a high rate, the capacity is still 515.3 mAh g -1 , which is at 2 A g -1 After 100 cycles at a current density of 1.34 mAh g -1 The specific capacity of the battery is 98%.
Citation Information
Patent Citations
High-entropy ferrite porous ceramic with surface modified with metal clusters as well as preparation method and application of high-entropy ferrite porous ceramic
CN115433019A